A full spectrum k-distribution based non-gray radiative property model for fly ash particles - Guo, Junjun; Hu, Fan; Luo, Wei; Li, Pengfei; Liu, Zhaohui (International journal of heat and mass transfer, 2018)
•A non-gray model based on weighted sum of gray particles is proposed.•Weighting factor and absorption efficiency are obtained from the k-distribution.•The model is valid for particle size of 1–150 µm, temperature of 500–2500 K.•Error less than 8% is achieved for non-isothermal inhomogeneous particle medium. Particle radiation characteristics have a strong wavelength-dependence. However, the gray particle assumption is widely used for coal combustion simulations, which cannot reflect the non-gray radiative property of the particles. In this study, based on the measured complex index of refraction from literatures (Gupta and Wall, 1985, Goodwin and Mitchner, 1989, and Lohi et al., 1992), a new non-gray particle radiative property model for fly ash is proposed by combining the features of full-spectrum k-distribution (FSK) model with the weighted sum of gray gases (WSGG) model. Four gray particles with different absorption and scattering efficiencies are used to replace the non-gray particles, for which absorption efficiency, scattering efficiency and weighting factor are directly obtained from the k-distribution, with model parameters obtained based on rational polynomials. Simultaneously, a gray particle model based on the Planck’s law is also obtained for comparison. The new model is systematically validated by comparing the radiative source terms and radiative heat fluxes, with those predicted by the line-by-line (LBL) integration of Mie-data in a one-dimensional plane-parallel slab system. The maximum relative error of radiative source term is 8% for the new non-gray radiative property model, 13% for Planck mean coefficients, 14% for modified Johansson model (Johansson, 2017), and 18% for empirical-constant model in non-isothermal inhomogeneous particle media, respectively. Combining the new non-gray radiative property model with the non-gray formulation of WSGG-SK model (Guo et al., 2015), the prediction accuracy is further validated by LBL solutions in the gas and particle mixture. Moreover, the contribution of gases and particles to radiative heat transfer is discussed at different path lengths, which shows the accuracy of the particle radiative property model determines the prediction accuracy of the radiative heat transfer in large-scale furnace.